Seasonal and interannual variations in the fatty acid composition of adult Euphausia superba Dana, 1850 (Euphausiacea) samples derived from the Scotia Sea krill fishery. Issue 6 (27th July 2018) - Ericson, Jessica A; Hellessey, Nicole; Nichols, Peter D; Kawaguchi, So; Nicol, Stephen; Hoem, Nils; Virtue, Patti
Abstract: The fatty acid content and composition of the Antarctic krill Euphausia superba Dana, 1850 were investigated using samples collected by a commercial fishing vessel. This dataset allowed comparison between seasons, years (2013–2016), and different fishing locations. Quantities of omega 3 fatty acids 20:5n-3 and 22:6n-3 (mg/g dry mass; DM) were highest in autumn and decreased through winter to reach a spring low. Quantities of the flagellate marker 18:4n-3 and diatom marker 16:1n-7c were variable and did not display the same seasonal fluctuations. In summer, krill had high percentages (% total fatty acids) of 20:5n-3 and 22:6n-3, total PUFA, and low 18:1n-9c/18:1n-7c ratios, indicating a more herbivorous diet. Krill became more omnivorous from autumn to spring, indicated by increasing ratios of 18:1n-9c/18:1n-7c and percentages of Σ 20:1 + 22:1 isomers. Bacterial fatty acids (Σ C15 + C17 + C19 isomers) were minor components year-round (0.9–1.8 %). Seasonal levels of herbivory and omnivory differed between years, and levels of specific fatty acid ratios differed between fishing locations. The fatty acid 18:4n-3 was a major driver of variability in krill fatty acid composition, with no obvious seasonal driver. This is the first study to report krill fatty acid data during all four seasons over consecutive years. This large-scale study highlights the value of using fisheries samples to examine seasonal and annual fluctuations in krill diet and condition.